Personality's Influence on Mood Variability and Leading Behavior. A Narrative Review - Kalogeratos, Gerasimos (Technium Social Sciences Journal, 2023)
The prevalence of mood swings in contemporary culture necessitates an examination of the influence of personality on the manifestation of associated symptoms and the inclination to address them. The current investigation entails a comprehensive literature assessment by examining scholarly papers from international bibliographic databases. The study examined the impact of individual traits and specific mental diseases on mood fluctuations, focusing on identifying patterns of enhancement or decline. The findings of these experiments indicate that this phenomenon has an impact on the temperament of every individual. Examining certain traits (extroversion, neuroticism, psychoticism, cockiness) yields insights into the extent to which these traits are either incorporated or excluded from the influencing elements, as well as the assessment of immediate emotional states. Hence, the significant significance of personality in the alteration of moods is acknowledged, given the distinctiveness of each individual and the examination of various aspects and traits associated with leadership.